Peran Humas dalam Transformasi Organisasi Perguruan Tinggi: Membangun Narasi Keberlanjutan melalui Komunikasi Formal di ULT Humas LLDIKTI Wilayah II (Triwikrama: Jurnal Ilmu Sosial, 2025)
The higher education sector is currently navigating a disruptive era that demands systemic transformation, placing Public Relations (PR) at the forefront of managing change and crafting narratives of sustainability. This study examines the strategic function of PR within the Integrated Service Unit (ULT) of LLDIKTI Region II, focusing on its role in facilitating institutional change and leveraging formal communication to reinforce long-term institutional credibility. Through descriptive qualitative methods—including observational fieldwork and in-depth interviews conducted during a February–June 2025 internship—the research highlights PR’s multifaceted contributions as an information hub, reputation architect, and mediator of stakeholder dialogue. Official digital platforms (websites, social media) and press releases serve as key tools to broadcast commitments to educational excellence, innovation, and societal impact. While bureaucratic hurdles persist, consistent formal communication proves pivotal in upholding LLDIKTI Region II’s legitimacy throughout its transformative evolution.